Analysis Factors of Motivation Among Adolescents in 3M Behavior During the Covid-19 Pandemic - Nurma Zela Gustina; Widyatuti Widyatuti; Musparlin Halid (Universitas Nahdlatul Ulama Surabaya, 2023)
Confirmed cases of COVID-19 in the adolescent are currently still happened. There needs to be motivation from teenagers to carry out 3M behavior to prevent the transmission of COVID-19, especially in the adolescent. This study aimed to identify factors related to adolescent motivation in carrying out 3M behavior during the COVID-19 pandemic. This study was conducted with a cross-sectional design of 427 adolescents in Palembang. The school sample was obtained using a random method, and respondents' determination was carried out purposively according to research inclusion criteria. Multiple linear regression analysis results showed that age, gender, education level, autonomy, policies, nurse support, and family support influenced adolescent motivation in carrying out 3M behavior during the pandemic (p = 0.000; 1 = 0.417; R2 = 0.651). The family support factor is the most influencing factor for adolescent motivation in carrying out 3M behavior during the COVID-19 pandemic (p = 0.000, 1 = 0.360) after being controlled by other variables (age, gender, education level, autonomy, policies, and nurse support). Knew the dominant factors is family suppot could increase health promotion program in an adolescent during the COVID-19 pandemic.